Tepelný průtokoměr - Mlčoch, Albert (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2022)
Práce se zabývá návrhem matematického modelu a praktickou realizací průtokoměru na tepelném principu. Rozsah navrhovaného průtokoměru je od jednotek kilogramů za hodinu do nižších stovek kilogramů za hodinu. Konstrukce průtokoměru je neinvazivní vůči průtokovému kanálu, topný element se nalézá vně trubky. V práci jsou identifikovány parametry průtokoměru a je navržen regulátor teploty. Na zkušebním přípravku jsou provedena měření. Výsledky měření jsou diskutovány. Jsou navrženy změny stávajícího hardwaru.

The thesis deals with the design of a mathematical model and practical implementation of a flowmeter based on the thermal principle. The range of the proposed flowmeter is from units of kilograms per hour to lower hundreds of kilograms per hour. The design of the flowmeter is non-invasive to the flow channel, the heating element is located outside the pipe. In this paper, the flowmeter parameters are identified and a temperature regulator is proposed. Measurements are made on a test bench. The results of the measurements are discussed. Modifications to the existing hardware are suggested.
Thermal Mass Flowmeter
Keywords: Anemometr; Kingova rovnice; měření průtoku; tepelný průtokoměr; COMSOL; tepelná vodivost; mikrokontrolér; vestavěný systém; PWM regulace; identifikace systému; nejistoty měření; Anemometer; King’s equation; flow measurement; heat flowmeter; COMSOL; thermal conductivity; microcontroller; embedded system; PWM regulation; system identification; measurement uncertainties